Pelatihan dan Pendampingan Website Desa Gelebak Dalam untuk Pengenalan Potensi Desa - Hellen Puspita Sari; Yesi Novaria Kunang; Eka Puji Agustini; Ilman Zuhriyadi; Irwansyah Irwansyah; Kurniawan Kurniawan (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Current village development cannot be separated from the support of information technology, in order to improve services to the community. One example is the existence of an internet program entering the village, the internet is currently not only enjoyed by urban communities but has reached rural communities. The difficulty of accessing existing information makes researchers interested in developing a website-based village information system with the aim of improving services to rural communities and access to information can be obtained easily. This website can improve services to the public so that information to the public can be accessed easily and accurately.